Childhood Obesity Trends among 8-11-Year-Olds: Insights from a School Sample in Vienna, Austria (2017-2023) - Paula Moliterno; Victoria Donhauser; Kurt Widhalm (MDPI AG, 2024)
In Austria, childhood obesity is a public health concern. This study examined time trends in the percentage of obesity among a sample of schoolchildren from Vienna (2017-2023). The body mass index percentiles of 326 children [9.3 years old (95% CI 8.3-10.5, min-max 8.0-10.9] from the EDDY study were calculated for trend analyses. Trend analysis was performed using a logistic regression using overweight and obesity as dependent binary variables, and study year and age as independent continuous variables. The percentage change over time was calculated, including the first period of the COVID-19 pandemic. Obesity percentages increased from 23.5 (95% CI 15.1-31.9)% in 2017 to 25.0 (95% CI 12.2-37.8)% in 2023. From 2017 to 2023, while overweight/obesity percentages decreased by 25.9 (−59.5-15.6)%, obesity increased by 6.4 (−51.2-94.9)%. A non-significant trend (p ≥ 0.38) was observed. During the first period of the pandemic, the percentage changes in overweight/obesity and obesity were 68.4 (5.6-187.9)% and 29.2 (−37.3-166.8)%, respectively. The current percentage of obesity in this sample is high and peaked in 2020 during the pandemic. These findings emphasize the need for future investigations considering the representativeness of the school-aged population in Austria to gain a broader picture of overweight and obesity trends.